Potensi Ekstrak Etanol Daun Petai (Parkia speciosa Hassk.) Terhadap Kadar Superoksida Dismutase (SOD) Pada Plasma Tikus yang Mengalami Stres Oksidatif - Butarbutar, Ruth Haryati; Robiyanto, Robiyanto; Untari, Eka Kartika (Pharmaceutical Sciences and Research, 2016)
Cigarette smoke is free radicals superoxide resources that contains, hydrogen peroxide, hidrosil and peroksil. Superoxide dismutase (SOD) is an enzymatic antioxidants that protect cells from oxidative stress by catalyzing superoxide dismutase (O2 *) into O2 and H2O2 . This study aims to determine the potential of ethanolic extract petai leaves against plasma SOD enzyme activity in animals exposed by cigarette smoke. The simplicia extracted by maseration using ethanol 96%. Thirty-six rats Sprague Dawley strain were divided into six groups: normal group was not given treatment, negative group received 10% CMC-Na, positive control group received vitamin E, and treatment group received ethanolic extract petai leaves of 50; 100; 250 mg / kgBW of mice. All rats were treated for 14 days. SOD activity was measured by UV-Visible spectrophotometer at a wavelength of 505 nm. Statistical analysis using One Way ANOVA. The mean value of SOD activity to the normal, negative control, positive control and the group receiving the ethanolic extract petai leaves dose of 50; 100; 250 mg/kg in a row is 37 979 ± 3708; 59 932 ± 3085; 48 552 ± 1234; 57 239 ± 2102; 50 774 ± 1632; 59 124 ± 4849. The results show ethanolic extract petai leaves the most influence on the activity of SOD is a dose of 100 mg/kg.